130 Injury analysis in mixed martial arts athletes. (3rd March 2020) - Zhang, Mandy; Lim, Baoying; Ho, Boon Hor; Tan, Benedict; Chew, Kelvin
Abstract : Background: Mixed martial arts (MMA) involves intensive sparring and utilize chopping, punching and grappling techniques. MMA participation is increasing and is associated with extreme physical injury to the opponent and confers significant risk of brain injury. Objective: To examine the types and location of injuries associated with MMA to decrease the risk of injuries during MMA. Design: Prospective descriptive single-cohort study. Setting: Professional MMA fighters of various weight classes; Injuries reported in the medical tent immediately after competition. Participants: The study included 85 professional MMA fighters who participated in MMA competitions in Singapore during September 2011 and May 2017. The study considered for inclusion only those who were diagnosed with injuries in the medical tent after the competition. Interventions/Assessment of risk factors: The majority of reported injuries occurred among males (88.2%). Main outcome measurements: Type of injury and location of injury, proportion of head-related injuries and severity of injury based on emergency department referral and subsequent admission in the hospital for further treatment. Results: The most common reported sites of injuries were the head (60.0%), followed by knee (6.4%) and arm (6.4%). The most common types of injuries were laceration (27.7%), contusion (26.9%) and concussion (12.6%). The most commonly occurring injuries to the head were laceration/contusion (67.3%), concussion (23.6%) and fractures (9.1%). Most injuries were managed acutely in the medical tent, with 30.6% being treated in the Emergency Department. Only 4.7% of athletes were admitted to the hospital. Conclusions: For achieving a knockout, the head is targeted in MMA, making it a high-risk location for injuries. Head and face injuries are the most common location of injuries. Lacerations, contusion and concussion are the most common diagnoses of injuries in competitive MMA athletes. Periodic evaluations about causes and types of injuries and advice on mitigating injury risk during competition as well as follow up for concussive symptoms should be recommended to reduce future risks of injury.